The impact of global mindset and cultural intelligence on international entrepreneurship intention of Vietnamese students - Nguyen, Thi Thu Thuy; Nguyen, Viet Hoang; Ha, Thu Hue; Nguyen, Thi Hau; Nguyen, Thi Thai Thuy; Tran, Tu Uyen (CENTRAL ASIA AND THE CAUCASUS, 2021)
The formation of a global mindset and the enhancement of cultural intelligence can play a role in developing students' international entrepreneurship intention. Therefore, the objective of this study is to clarify this relationship at universities in Vietnam. We employed a partial least squares structural equation model (PLS-SEM) to estimate the responses of 201 students to test the impact of global mindset and cultural intelligence on international entrepreneurship intention. Furthermore, this study also tests the mediating role of entrepreneurial self-efficacy on the impact from global mindset and cultural intelligence to international entrepreneurship intention. Multigroup analysis techniques and assessment of moderating roles were also used to clarify the impact of factors on international entrepreneurship intention. A positive effect of global mindset and cultural intelligence on international entrepreneurship intention was found and entrepreneurial self-efficacy also had positively mediating roles on this relationship. In addition, there are differences in the impact of cultural intelligence on international entrepreneurship intention by sex group (male, female) and at the same time, global mindset and study year also play a role in moderating the impact from cultural intelligence to international entrepreneurship intention. Therefore, schools and start-up support organizations should have plans to strengthen CQ and GM to increase students' intention to start a business.